GENERALIZED IDENTITIES OF BIVARIATE FIBONACCI AND BIVARIATE LUCAS POLYNOMIALS - Jaya Bhandari; V. K. Gupta; Yashwant Panwar (Journal of Amasya University the Institute of Sciences and Technology)
In this paper, we present generalized identities of bivariate Fibonacci polynomials and bivariate Lucas polynomials and related identities consisting even and odd terms. Binet’s formula will employ to obtain the identities. Also we describe and derive sums and connection formulae.